2020
DOI: 10.1029/2020jb019536
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Segregation in Granular Mass Flows With Different Ambient Fluids

Abstract: Size segregation, which is a robust feature of sheared granular mixtures and geophysical mass flow deposits, is found to diminish in the presence of a viscous fluid. We study this inhibitive effect through coupled fluid-particle simulations of granular flows fully immersed in different ambient fluids. Granular-fluid mixture flows are modeled according to three distinct flow regimes-free fall, fluid inertial, and viscous-at different angles of inclination. Each flow regime corresponds to distinct flow dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 85 publications
(218 reference statements)
1
33
1
Order By: Relevance
“…4. Note that these values are significantly higher than those reported in [9] due to different partitioning criteria applied [12].…”
Section: Analysis Using Stress Partitioningcontrasting
confidence: 54%
“…4. Note that these values are significantly higher than those reported in [9] due to different partitioning criteria applied [12].…”
Section: Analysis Using Stress Partitioningcontrasting
confidence: 54%
“…The pioneering work of Savage and Lun (1988) through buoyancy as a function of  . Our recent work (Zhou et al, 2020) showed that size segregation in immersed granular flows over rough inclines (Figure 10a) is inhibited due to the weakening of contact pressures owing to buoyancy and due to the low shear rates resulting from the development of plug zones induced by an opposing streamwise drag. Three distinct ambient fluids: air, water, and a viscous "slurry" (a fluid 500 times more viscous than water but having the same density), were considered.…”
Section: Percolation Velocity In Immersed Gravity-driven Flowsmentioning
confidence: 99%
“…However, Figure 10c shows that scaling by I is inadequate to collapse the data, as fluid-related mechanisms that govern the difference in the segregation behavior are not fully considered. Here, with the scaling established in this paper, it is possible to revisit the data in Zhou et al, (2020) and show whether the proposed scaling works for different flow scenarios.…”
Section: Percolation Velocity In Immersed Gravity-driven Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grain size segregation in debris flow also affects the movement process (Iverson et al, 2010). Studies have shown that grain size segregation has a profound impact on the mobility of immersed granular flows, and is strongly associated with the pore pressure distribution (Bagnold, 1954;Middleton, 1970;Remaitre et al, 2011;Jing et al, 2017;Cui et al, 2020;Zhou et al, 2020). In the granular flow and geophysical flow communities, the mechanism of the development of pore water pressure and its critical role in determining mobility have been widely concerned, and some quantitative relationships have been obtained (Iverson, 2005;Rondon et al, 2011;Meruane et al, 2012;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%